Kura in Motion, Azerbaijan and Georgia: Landscape investigations - Ricci, Andrea (e-Forschungsberichte des DAI, 2023)
This report summarizes the summer 2013 archaeological landscape activities in Azerbaijan and Georgia as part of the French-German ANR-DFG “Kura in Motion” project. With the aim of exploring human-environment dynamics for the entire course of the Holocene, another 77 previously unknown occupations could be mapped by an intensive survey at the Mil Plain in southwest Azerbaijan. Several of these sites are small in dimensions and date to the late Neolithic period (6th millenium BC). Later remains include Chalcolithic, Iron Age and Medieval artifacts. In the Kvemo-Kartli region of southeast Georgia, prehistoric landscape with local late Neolithic materials retrieved on five locations could be studied.